Assessing trophic adaptability is critical for understanding the response of predatory fishes to climate change: a case study of Pomatomus saltatrix in a global hotspot. Issue 4 (2nd December 2016) - Potts, WM; Bealey, RSJ; Childs, A-R
Abstract : There is a growing need to incorporate biotic interactions, particularly those between predators and their prey, when predicting climate-driven shifts in marine fishes. Predators dependent on a narrow range of prey species should respond rapidly to shifts in the distribution of their prey, whereas those with broad trophic adaptability may respond to shifts in their prey by altering their diet. Small pelagic fishes are an extremely important component of the diet of many marine predators. However, their populations are expected to shift in distribution and fluctuate in abundance as the climate changes. We conducted a comparative study of the seasonal diet of adult Pomatomus saltatrix over two periods (June–December 2006 and 2012) and examined the available data on small pelagic fishes biomass in a global hotspot (the coastal region of southern Angola, southern Africa) to gain an understanding of the tropic adaptability of the species. Despite a drop (630 000 t to 353 000 t) in the abundance of their dominant prey ( Sardinella aurita ) in the region, it remained the most important prey item during both study periods (Period 1 = 99.3% RI, Period 2 = 85.3% RI, where %RI is a ranking index of relative importance). However, the diet during Period 2 was supplemented with prey typically associated with the nearshore zone. The seasonal data showed that P. saltatrix were capable not only of switching their diet from S. aurita to other prey items, but also of switching their trophic habitat from the pelagic to the nearshore zone. These findings suggest that P. saltatrix will not necessarily co-migrate if there is a climate-driven shift in the distribution of small pelagic fishes (their dominant prey). Accordingly, understanding the trophic adaptability of predators is critical for understanding their response to the impacts of climate change.